Understanding meaningful symptoms and challenges in people with Down syndrome and dementia: A qualitative study of caregivers' perspectives: Human/Novel outcomes measures. (7th December 2020) - Knox, Kari; Stanley, Justin; Hendrix, James A; Hillerstrom, Hampus; Achenbach, Jillian; Chicoine, Brian; Lai, Florence; Lott, Ira T; Rockwood, Kenneth
Abstract: Background: People with Down syndrome are at an increased risk of developing Alzheimer's Disease. As many more individuals with Down syndrome are now living into older adulthood, the prevalence of Alzheimer's disease has risen significantly in this group. Identifying dementia symptoms in this setting can be daunting due to heterogeneous baseline function, cognition, and behaviour. Here, we interviewed caregivers to elicit their impressions of the most meaningful symptoms and challenges for people with Down Syndrome and dementia. Method: Initially, a dementia symptom menu was adapted for Down syndrome by four expert clinicians. We then recruited 10 caregivers of people with Down syndrome and dementia. Semi‐structured interviews began with open‐ended discussion of symptoms and challenges, followed by an in‐depth menu review. Interviews were facilitated by a research nurse, audio recorded and transcribed verbatim. Transcripts were reviewed by two researchers who coded quotes independently. Codes were discussed to identify emergent themes. Result: Caregivers ranged from 54‐77 years of age (median 65). Most were female (9/10) with ≥15 years of education (10/10). The person they cared for was 52‐61 years (median 58) with Down syndrome and a formal diagnosis (6/10) or clinical suspicion (4/10) of dementia. Chiefly, two themes were identified: caregiver burden and healthcare difficulties. Caregiver burden was expressed in many ways such as increased responsibilities, financial impact and emotional toll. Caregivers also described challenges with medical professionals who were not well‐equipped for these patients ("One [physician] was very honest with me and said 'I have to tell you; I have no clinical experience with this'"). This was particularly noted by caregivers in rural areas. When asked to list their five most meaningful symptoms, caregivers reported behavioural changes (13/50, e.g. irritability/frustration) followed by cognitive decline (12/50, e.g. verbal repetition) and physical manifestations (11/50, e.g. incontinence). Conclusion: In eliciting views about the most meaningful symptoms and challenges, semi‐structured interviews identified two main themes: caregiver burden and healthcare difficulties. Although in people without Down syndrome cognitive decline is the hallmark of dementia, here caregivers interviewed frequently reported changes in behaviour and physical manifestations as most meaningful.